AN ANALYTICAL STUDY OF TRANSLATION EDITING AND TRANSLATION PROCESS OF THE CHILDREN’S LITERATURE “THE LION THE WITCH AND THE WARDROBE” - เครือโชติ, สมพิศ (Journal of Educational Review Faculty of Education in MCU, 2019)
The aim of this research was to study the type of translation editing and translation process in C.S. LEWIS’s children’s literature “The Lion the Witch and the Wardrobe”, in Thai translated version by Soommana Boonyarattawech. The researcher applied the principles of translation editing by Sanchwi Saibua (2010) to analyze the 17 examples. The finding were classified into two levels, which were adjustment in the word level and language structure level. The result indicated that in the word level, using word and idioms deletion was used most frequently. In terms of language structure level, the two most frequently found types were adding and deletion of word in sentence or rearrangement of word order in sentence or phrase. In general, the translator mostly used literal translation technique in order to keep meaning closely to the original version and natural flow as well.